ECONOMIC DEVELOPMENT OF ULTRA-SMALL PERIPHERAL WEST EUROPEAN REGIONS (CASE OF ÅLAND AND FAROE ISLANDS) - Efimova, Elena G.; Kuznetsova, Natalia P. (Ekonomika, 2012)
The aim of the study was identification of ultra-small territories, features of their economic development and modern business status in the context of the classification of small economies. The object of investigation is small economies of West European and Nordic countries as well as ultra-small autonomous territories of Åland and Faroes islands affiliated to Finland and Denmark, respectively. The hypothesis of the article is that ultra-small autonomous territories under consideration are developing as the “competitive sub-peripheries” due to their special industrial organization, stimulated by the national and, partially, by the EU economic policy supporting the economic growth of both autonomies. The methods of the study comprise analysis–synthesis, historical and logical methods, international comparisons. The main conclusion is that the Åland and Faroes islands are nowadays converting into the transport-logistics, informational, financial bridges among different European regions and countries.